Analysis of User Experience and User Satisfaction of the Satwagia Mobile Application - Elai Novita Mariani Banurea; Siti Jahroh; Yudha Heryawan Asnawi (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2026)
The development of digital technology in Indonesia has encouraged various sectors to transform towards digital-based services, including the animal health industry. Satwagia Mobile is an application designed to provide digital pet health and care services, including online consultations, vaccination bookings, grooming, and pick-up and drop-off services. This study aims to analyze the user experience (UX) and user satisfaction with the Satwagia Mobile application. The research method used a quantitative approach with primary data collection through an online survey using a Google Form questionnaire. The study sample consisted of 100 respondents who had made at least two transactions on the Satwagia Mobile application. The results showed that the user experience was generally in the fairly good category, with the highest scores in the Stimulation (3.10) and Perspicuity (3.09) dimensions, indicating that users felt motivated and easily understood the application's instructions. However, the Efficiency (2.97) and Dependency (2.90) dimensions still require improvement, particularly in service speed and flexibility in selecting a veterinarian. The user satisfaction level was in the fairly satisfied category (2.91), indicating potential for development to improve service convenience, reliability, and innovation. These findings are expected to be input for Satwagia Mobile developers in improving the quality of user experience and satisfaction.